The Role of Intellectual Capital in Organizational Innovation (A Field study on Industrial Organizations in Latakia Governorate) - محمد, رامي; سامر أحمد قاسم , (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The aim of this research is to determine the role of intellectual capital in organizational innovation in industrial organizations in Latakia Governorate by determining the relationship between the dimensions of intellectual capital (human capital, structural capital, relational capital) and organizational innovation in a sample of industrial organizations in Latakia Governoratee. The researcher relied on the deductive approach as a general method of thinking and the descriptive analytical method as a general approach to research. The researcher designed a questionnaire as a tool for collecting primary data. The questionnaire was distributed to a sample consisting of (115) workers in the organizations sampled for the study. (109) questionnaires were retrieved and there were (103) questionnaires valid for statistical analysis. The statistical analysis program (SPSS25) was relied upon for data analysis. the research reached a set of results, the most important of which were: There is a significant relationship between intellectual capital and organizational innovation for workers in industrial organizations in Latakia Governorate. The industrial organizations in the study sample possess intellectual capital to a moderate degree, and the level of organizational innovation is a moderate in the organizations in in Latakia Governorate.